Variations of the chemical composition and bioactivity of essential oils from leaves and stems of Liquidambar styraciflua (Altingiaceae). (30th September 2013) - El‐Readi, Mahmoud Z.; Eid, Hanaa H.; Ashour, Mohamed L.; Eid, Safaa Y.; Labib, Rola M.; Sporer, Frank; Wink, Michael
Abstract Objectives This study aimed to evaluate the variations of the chemical composition and bioactivity of essential oils of Liquidambar styraciflua L. (Altingiaceae) collected in different seasons. Methods The oils were analysed by GLC/FID and GLC/MS. The antioxidant activity was investigated by diphenylpicrylhydrazyl (DPPH) and superoxide anion radical scavenging assays and the deoxyribose degradation assay. Inhibition of both 5‐lipoxygenase (5‐LOX) and prostaglandin E2 (PGE2) production in hepatic cancer (HepG‐2) cells were used to assess the anti‐inflammatory activity. The cytotoxic activity was investigated using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay. Key findings Altogether, 64 volatile secondary metabolites were identified. The major components of the leaf oil were d‐limonene, α‐pinene and β‐pinene, and of the stem oil were germacrine D, α‐cadinol, d‐limonene, α‐pinene, and β‐pinene. Leaf and stem oils collected in spring could reduce DPPH● (IC50 = 3.17 and 2.19 mg/ml) and prevent the degradation of the deoxyribose sugar (IC50 = 17.55 and 14.29 μg/ml). The stem oil exhibited a higher inhibition of both 5‐LOX and PGE2 than the leaf oil. The cytotoxic activity of leaf and stem oils was low in cancer cell lines (IC50 = 136.27 and 119.78 μg/ml in cervical cancer (HeLa) cells). Conclusions Essential oils of L. styraciflua exhibited an interesting anti‐inflammatory activity with low cytotoxicity, supporting its traditional use to treat inflammation.